A review of progress and applications of ship shaft-less rim-driven thrusters. (1st November 2017) - Yan, Xinping; Liang, Xingxin; Ouyang, Wu; Liu, Zhenglin; Liu, Bao; Lan, Jiafen
Abstract: The shaft-less rim-driven thruster (RDT) has become an attractive ship propulsion device in the marine industry in recent years, as it can provide many advantages over traditional ship propulsion plants including reduced vibration and noise, enhanced onboard comfort and propulsion efficiency, flexible installation locations arrangement, light weight and compact size. This paper reviews the latest research focuses, progress and applications of RDT. Theoretical and experimental research on the design, performance analysis and control of the RDT are discussed, including electric motor, bearings structure, hydrodynamic optimization, and coupling design between RDTs and ship hull. Typical application cases of RDTs are introduced, and a statistic for the worldwide commercial RDT companies and the key parameters of their typical products is given. High-power RDT technology remains generally unsophisticated; the performance and reliability of the RDTs need to be further improved, especially in regards to the development of high-power and low-speed electric motors, electromagnetic-thermal-fluid-solid coupling research, high power RDT cooperative design method, vibration and noise control, the improvement of anti-fouling and anti-damage capability, multiple RDTs cooperative control method. The advantages of RDT make it a potentially highly effective and economical choice for a wider range of ships than other propulsion alternatives in the future. Highlights: We review the research progress of shaft-less Rim Driven Thruster (RDT) in terms of both theoretical and experimental studies on driven motor performance, motor control systems, hydrodynamic performance, and optimization. Several application cases are enumerated. Future research directions are proposed.